Mollusk Community (Gastropods and Bivalves) in Suli Coastal Waters, Central Maluku, Indonesia - Haumahu, Sara; Uneputty, Prulley A.; Supusepa, Junita (Masyarakat Moluska Indonesia, 2025)
Gastropods and bivalves are benthic organisms from molluscs’ phylum. These organisms play an important role in aquatic ecosystems such as grazer, detritus feeder, predator. Some species have economic important value. Suli coastal water has higher diversity of marine molluscs, which is used by local community as protein sources besides fishes. This resource faces threats due to utilization activities by the community during the low tide period. The objectives of this research are to analyze community structure of this mollusc including species composition, ecological density, potency, frequency of occurrence, ecological index of communities, as well as to analyze the distribution pattern of this marine mollusc. This study was conducted in December 2023 in the intertidal zone of Suli coastal watesr with applying transect line methods during the day at low tide period. The total of 719 individual marine gastropods collected in this study area consisted of five orders, 19 family, 36 genera and 50 species. The highest ecological density and potency of gastropods belong to Monetaria annulus and Rochia nilotica. In other hand, as much as 147 individuals of bivalves found in this area, which is included in six order, 10 family, 16 genera dan 20 species. Anadara antiquata, and Balbatia decusatta have the higher ecological density and potency, while Trachicardium subrugossum, Anadara antiquata, and Dosinia contracta have the higher frequency of occurence. The diversity of gastropod and bivalve in this study area is in medium category, evenness index is high category and lowest dominance index. Marine gastropods and bivalves showed the clumped distribution pattern.